IMPLEMENTASI PEMBELAJARAN NILAI PENDIDIKAN ISLAM MELALUI BCM ( BERMAIN, CERITA, BERNYANYI ) DI RA MASYTHOH ANGDONGSILI WONOSOBO - Munawaroh, Hidayatu (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2018)
The purpose of this study was to find out and describe the application of the BCM method in learning the value of Islamic education in RA Masythoh Andongsili Wonosobo. This research is a qualitative descriptive study. Data collection is done using the method of observation, interviews and documentation. Data collection is done by digging data sources, namely the Head of RA and RA teacher, as well as direct observation of the process of applying the BCM method in learning the value of Islamic education in RA Masythoh Andongsili Wonosobo. The results of the study showed: 1. The playing method used in learning the value of Islamic education through the game of Children Sholeh, Pat the Pillars of Islam, Pat the Pillars of Faith, and Pat the Angels. As well as guessing images of God's creations that are on earth and in the sky. 2. Method The story used in learning the value of Islamic education is the story of the Noble Traits of the Apostle of Allah, and the story of the Tasks of the Angel Roqib and the Angel of Atid. 3. The singing method used in learning the value of Islamic education is by eating adab songs, songs of Allah Almighty, Little Star songs, Rainbow songs, Kitab Allah songs, Lord Esa songs, and the songs of 10 Angels of Allah.